2019
DOI: 10.1504/ijenvh.2019.108681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium on the behaviour of Cnesterodon decemmaculatus

Abstract: Recognising biomarkers for assessing early ecotoxicity effects using test species exposed to reference toxicants is important, hence the aim of this work was to study changes in some behavioural parameters of Cnesterodon decemmaculatus. Fish were under stress conditions induced by exposure to a subtoxic concentration of cadmium (Cd) in the laboratory. Acute bioassays (96 h) were performed under laboratory conditions, with medium renewal every 48 h. Animals were randomly assigned into two groups of 10 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…It is worthy to mention the importance of analyzing data by sex for a more precise evaluation of behavioral parameters, which otherwise may be affected by significant data dispersion. Sexual behavior differences have been reported for C. decemmaculatus exposed to cadmium in ecotoxicological studies (Ferro, 2017, 2019) and we observed that As altered the acceleration and maximum velocity in females. The present study showing a differential effect of As on the swimming behavior of males and females provides a preliminary baseline to be used in future behavioral studies and in environmental monitoring.…”
Section: Discussionsupporting
confidence: 74%
“…It is worthy to mention the importance of analyzing data by sex for a more precise evaluation of behavioral parameters, which otherwise may be affected by significant data dispersion. Sexual behavior differences have been reported for C. decemmaculatus exposed to cadmium in ecotoxicological studies (Ferro, 2017, 2019) and we observed that As altered the acceleration and maximum velocity in females. The present study showing a differential effect of As on the swimming behavior of males and females provides a preliminary baseline to be used in future behavioral studies and in environmental monitoring.…”
Section: Discussionsupporting
confidence: 74%